Features of Singing in Chinese Pop and Traditional Music: the Influence of the Music Genre on Vocal Music - Hu, Mu (Música Hodie, 2023)
Musical compositions require genre-specific sophisticated performance techniques. This paper focuses primarily on the features of Chinese pop and traditional music, based on the music genre’s influence on the vocal music. To achieve this goal, the analysis methods and the Shapiro-Wilk test were used. The study involved 218 music major students from the Beijing International Art School, Shanghai Normal University, and Guangzhou College of Music. The audience and respondents gave less preference to pop music (47% and 39%) compared to the traditional music (53% and 61%). The Shapiro-Wilk test revealed that, when it comes to pop music, the strongest preference was attributed to music geographical spread (0.867), and in the case of traditional music the strongest preference was for higher education (0.927). The paper established the specific features of different genres of music. The most common elements pertaining to pop music include: the option to apply a variety of music elements and singing techniques; rhythm stability; a simple form of vocal performance; extreme sound techniques; preserving the emotionality of the singing; a combination of Western and Chinese elements. Traditional music is characterized by a harmony of music elements and voice timbres, maintenance of the high-pitched voice, natural sound, throat singing, performance quality, preservation of Chinese traditional music elements. Traditional music instruction was the best thing for improving intonation (0.815), maintenance of sound quality (0.806), and development of vocal range (0.718). Pop music is known for a combination of various music elements (0.901), conveyance of the performance style (0.312). The paper’s practical implications boil down to determining the characteristic features of pop and traditional music, as well as elements describing vocal music. Further studies might involve a comparative analysis between Chinese pop music, traditional music, and Western pop and traditional music.